2019
DOI: 10.1186/s12957-019-1746-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of complete cytoreduction with concurrent liver resection followed by hyperthermic intraperitoneal chemotherapy for synchronous peritoneal and liver metastatic colorectal cancer

Abstract: BackgroundThis study aimed to evaluate the clinical outcomes of concurrent liver resection with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in colorectal cancer patients with synchronous liver and peritoneal metastases.MethodsPatients with colorectal liver and peritoneal metastasis who underwent complete cytoreduction and hyperthermic intraperitoneal chemotherapy with concurrent liver surgery between September 2014 and July 2018 were included. Perioperative outcomes, overall survival, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…However, no data were available to clarify the risk factors to determine the difference in morbidity. Our results are in line with the findings of Cloyd et al ( 35 ), who described that concomitant LR and CRS/HIPEC were associated with an increased number of postoperative complications and increased readmission compared to patients undergoing CRS/HIPEC alone. However, contradictory results of single-institution studies reporting no difference in postoperative morbidity have been published ( 3 , 23 , 27 , 33 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, no data were available to clarify the risk factors to determine the difference in morbidity. Our results are in line with the findings of Cloyd et al ( 35 ), who described that concomitant LR and CRS/HIPEC were associated with an increased number of postoperative complications and increased readmission compared to patients undergoing CRS/HIPEC alone. However, contradictory results of single-institution studies reporting no difference in postoperative morbidity have been published ( 3 , 23 , 27 , 33 ).…”
Section: Discussionsupporting
confidence: 93%
“…In most of the studies, the PCI was comparable, and in all cases, it was below 20, which corresponds with clinical guidelines ( Table 2 ). With the exception of the studies by Pinto et al ( 28 ), Lo Dico et al ( 40 ), and Jeon et al ( 35 ), the studies in this review presented patients treated in a one-step procedure with CRS–HIPEC and liver resection/ablation performed during the same surgical procedure. Only a few studies reported the number of liver lesions.…”
Section: Resultsmentioning
confidence: 96%
“…In total, 3137 patients participated in 2 case-control studies, 11 prospective studies, and 7 retrospective cohort studies. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] No randomized studies were identified. Although the search and selection process was designed to include various oligometastatic sites, the studies that met the criteria for inclusion all presented liver metastases.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Moreover, about 25% of patients diagnosed with localized CRC are at elevated risk for metastatic progression in the later course of the disease. In Korea, approximately 15–25% of the patients show synchronous metastases and 30–40% of them have unresectable liver metastasis [ 2 ]. Ultimately, 50–60% of patients present with mCRC, including recurrent metachronous CRC [ 3 ].…”
Section: Introductionmentioning
confidence: 99%